2010
DOI: 10.1016/j.ecss.2009.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fish trophic levels in an estuarine system

Abstract: The concept of trophic level is particularly relevant in order to improve knowledge of the structure and the functioning of an ecosystem. A precise estimation of fish trophic levels based on nitrogen isotopic signatures in environments as complex and fluctuant as estuaries requires a good description of the pelagic and benthic trophic chains and a knowledge of organic matter sources at the bottom. In this study these points are considered in the case of the Gironde estuary (south west France, Europe). To obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 64 publications
7
38
0
6
Order By: Relevance
“…This may indicate fishing down the food web as a result of overfishing pressure. Pasquaud et al (2010) reported similar range of trophic levels (2.8-3.9) from an estuarine fishery as reported here. However, McClanahan and Mangi (2004) reported hook fishermen as landing higher trophic level fishes (3.6) compared to basket trap (2.5) and other gears (> 2.5).…”
Section: Discussionsupporting
confidence: 70%
“…This may indicate fishing down the food web as a result of overfishing pressure. Pasquaud et al (2010) reported similar range of trophic levels (2.8-3.9) from an estuarine fishery as reported here. However, McClanahan and Mangi (2004) reported hook fishermen as landing higher trophic level fishes (3.6) compared to basket trap (2.5) and other gears (> 2.5).…”
Section: Discussionsupporting
confidence: 70%
“…Berbagai pendekatan yang telah berkembang dalam memahami jejaring trofik, berawal dari pengamatan langsung terhadap isi lambung dari setiap individu hingga pada akhirnya dapat menentukan jenis makanan pada tingkat populasi (Pasquaud et al, 2009). Pasquaud et al (2009) juga menyatakan bahwa pendekatan yang lebih baru dengan menggunakan teknik isotop stabil untuk menentukan aspek-aspek kualitatif dan kuantitatif dari dinamika dan struktur jejaring trofik. Studi lain dengan menggunakan berbagai teknik untuk mengevaluasi interaksi mangsa-pemangsa (prey-predator) dan dinamika dalam transfer dan aliran energi (Zetina-Rejón et al, 2003;Sá et al, 2006;Haputhantri et al,2008).…”
Section: Pendahuluanunclassified
“…This method is convenient because it can be carried out rapidly and economically, providing a direct estimation of prey contents (Hyslop, 1980;Pasquaud et al, 2010;Winemiller et al, 2011). However, stomach content analysis has some limitations, because living organisms digest food more rapidly than non-living organic matter (Fry and Ewel, 2003).…”
Section: Proportional Contribution Of Dz In the Diet Of Consumersmentioning
confidence: 99%
“…As a result, there has been an increasing number of studies using dual stable carbon and nitrogen isotopes to determine the relationship between predators and their food sources (Fry, 2007;Nakamura et al, 2008;Pasquaud et al, 2010;Vinagre et al, 2012;Tue et al, 2013). The δ 15 N in the tissues of a consumer is typically 2.6‰ to 3.4‰ richer than that in their prey; thus, δ 15 N studies are often conducted to estimate the trophic position of species in the food web (Deniro and Epstein, 1981;Post, 2002;Fry, 2007).…”
Section: Introductionmentioning
confidence: 99%